Право на інформацію про безпеку та якість харчових продуктів - Ільїна, О. В.; Ilina, O. V. (Право і безпека. - 2013. - № 4 (51). - С. 147-151, 2013)
З використанням методів системного аналізу, узагальнення, абстрагування, порівняння, дедукції з’ясовано сутність права на інформацію про безпеку та якість харчової продукції в їх системному зв’язку з поняттям «право на інформацію». Запропоновано авторське визначення права на інформацію про безпеку та якість харчових продуктів, означено механізм його реалізації. Визначено напрями подальшого розвитку суспільних відносин у цій сфері.

Objective. Research of scientific views about the issue of determining the right for information about foods’ safety and quality; research of the mechanism of its realization, identification of priority areas for further development of public relations in the sphere of access to information about foods’ safety and quality. Methodology. General scientific methods of research such as system analysis, generalization, abstraction, comparison are used in the paper. The method of deduction is also used while characterizing the notion the right for information about foods’ safety and quality based on the features of general concept of the right for information. Results. The essence of the right for information about foods’ safety and quality in their system relation with the concept «right for information» is found out; research of the mechanism of its realization is conducted; on the basis of the research priority areas for further development of public relations in the sphere of the access to information about foods’ safety and quality are formulated. Scientific novelty. Scientific positions on defining the notion of the right of access to information about foods are improved. The author’s definition of the right for information about foods’ safety and quality is offered and tendencies of public relations development in the research area are defined. The practical significance. The usage of suggested approaches in defining the right for information about foods’ safety and quality will allow: to single out and properly enshrine in legislative sources the outgoing provisions of forming and functioning the mechanism of realization of the right for information about foods’ safety and quality in lawmaking practice; to take decision on the state of guaranteeing to ensure an adequate level of health protection and consumer interests, their awareness, establishing the means of guaranteeing consumers right for information and procedures of providing information about foods in enforcement practice.

С использованием методов системного анализа, обобщения, абстрагирования, сравнения, дедукции выяснена суть права на информацию о безопасности и качестве пищевой продукции в их системной связи с понятием «право на информацию». Предложено авторское определение права на информацию о безопасности и качестве пищевых продуктов очерчен механизм его реализации. Определены направления дальнейшего развития общественных отношений в этой сфере.
The right for information about foods’ safety and quality
Право на информацию о безопасности и качестве пищевых продуктов
Keywords: інформація; право на інформацію; доступ до інформації; харчовий продукт; якість; information; right for information; access to information; safety and quality of foods; information about foods’ safety and quality; информация; право на информацию; доступ к информации; пищевой продукт; безопасность; качество